Jelena Dimitrijević’s novel Nove in the Context of Literary Awards (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In the attempt to point to the literary and historical significance of Jelena Dimitrijević’s novel Nove, this paper investigates the inconsistencies surrounding the prize allegedly awarded for this novel, which is a piece of information that has been reappearing in academic discussions for more than a century. Upon examining the texts that mention the Matica srpska Prize, the essay rejects this possibility, quoting the relevant minutes of this institution. The essay proceeds to examine a much more frequent and, in all likelihood, older piece of information – that the prize was awarded by Srpska književna zadruga [Serbian Literary Cooperative], which published the novel. The results of this study largely confirm the authors’ hypothesis that the publication itself was later incorrectly interpreted as a separate prize. The key evidence supporting the hypothesis is to be found in Istorija Srpske književne zadruge [The History of the Serbian Literary Cooperative], which states that four manuscripts arrived in response to their call for submissions, specifying that the accepted manuscript – Jelena Dimitrijević’s Nove – was printed as any other work, not as the winner of the literary competition.
Keywords: Jelena Dimitrijević; novel Nove; literary prize; Srpska književna zadruga [Serbian Literary Cooperative]; Matica srpska